2016
DOI: 10.1017/s0014479716000302
|View full text |Cite
|
Sign up to set email alerts
|

Sixty Years of Breeding in Cameroon Improved Fibre but Not Seed Cotton Yield

Abstract: SUMMARYSeed cotton yield in Northern Cameroon has been declining since the 80s despite breeding efforts. In order to evaluate the impact of genetic improvement on this decline, we conducted field experiments in two locations with 10 widely grown cotton cultivars released in Cameroon between 1950 and 2009. The rate of genetic gain (GG) was estimated with a linear regression of the cultivar mean on its year of release (YR). Contrasts between rates of GG observed with different planting dates were estimated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
3
2
0
1
Order By: Relevance
“…Acquaah (2011), in line with the present study, mentions that changing planting dates and crop varieties are the frequently preferred adaptation strategies by smallholder farmers in Morogoro, Tanzania. This is in accordance with a similar studies by Singh et al (2014), on peanuts and cotton in West Africa (Loison et al 2017), while, Hammer et al (2002, argue that it is only partially true, since shifting in these indicators should reflect genetic variability.…”
Section: Changing Planting Dates and Shortening Cycle Crop Varietiessupporting
confidence: 90%
See 1 more Smart Citation
“…Acquaah (2011), in line with the present study, mentions that changing planting dates and crop varieties are the frequently preferred adaptation strategies by smallholder farmers in Morogoro, Tanzania. This is in accordance with a similar studies by Singh et al (2014), on peanuts and cotton in West Africa (Loison et al 2017), while, Hammer et al (2002, argue that it is only partially true, since shifting in these indicators should reflect genetic variability.…”
Section: Changing Planting Dates and Shortening Cycle Crop Varietiessupporting
confidence: 90%
“…Changing planting dates decreases the effects of crop damage or loss from prolonged weather conditions, such as, extreme drought and dry spells, causing an epidemic of crop diseases and insect pests-which in turn result in poor harvests and food insecurity. Similar studies conducted in the Lilongwe District, concluded that farmers in Sub-Sahara Africa, especially, in hot and dry regions, if they plant crop varieties that have short duration for maturity (within 2-3 months), this allows farmers to minimize and evade the damaging effects of moisture-stress on crop yields (Zinyengere et al 2014), These narrative are also consistent with studies conducted on groundnuts and cotton, in West Africa (Loison et al 2017;Singh et al 2017).…”
Section: Changing Planting Dates and Shortening Cycle Crop Varietiessupporting
confidence: 81%
“…Although our results are favorable to cotton production in Venezuela, the rate of increase of the different traits studied were similar to those reported by Schwartz and Smith (2008), Loison et al. (2017), and Zhang et al. (2019) for different environmental conditions.…”
Section: Resultssupporting
confidence: 92%
“…Since the 1970s, there have been numerous studies on genetic gains or long-term trends in LY, yield components, fiber quality, and other traits in the United States (see the summary in the introduction) and some other countries (Zhang et al, 1993;Liu et al, 2013;Rochester and Constable, 2015;Loison et al, 2017). The present study supported previous reports of an upward trend from 1.2 to as high as 20.6 kg ha −1 yr −1 for LY improvement since the turn of the 20th century (Culp and Green, 1992;Bayles et al, 2005), depending on tests, states and regions, breeding programs, production periods, or conditions (Meredith et al, 1997;Calhoun and Bowman, 1999;Meredith, 2000;Smith.…”
Section: Discussionmentioning
confidence: 99%